Application of the Drill Method to Improve the Learning Outcomes of Class V Elementary School Students in Mathematics Subjects - Sinaga, D. Yuliana; Sirait, Esti Marlina (Cattleya Darmaya Fortuna, 2022)
Based on the phenomenon that often occurs in the fifth grade of elementary school in mathematics, there are students' difficulties in understanding these subjects. In the study, there were several problems that students tended to be passive, only a small number of students were active in participating in learning. The process of learning mathematics in class V SD Negeri 015906 Lubuk Palas tends to be not optimal. This is because students do not understand the material and some students are not able to work on various questions so that student learning outcomes are still low. The purpose of this study was to improve the learning outcomes of fifth grade students in mathematics. The results of the study by applying the drill method to the fifth grade mathematics subject in the first cycle, obtained 43.47% of students who completed. in the second cycle the student learning outcomes who completed as much as 65.21% completeness learning outcomes have increased by 21.74% and have met the KKM standard 70 reaching 65.21% at the end of the cycle. From the results of this study, it can be seen that student learning outcomes have increased, it can be concluded that learning by optimizing the drill method can improve student learning outcomes in mathematics for fifth grade students at SD Negeri 015906 Lubuk Palas.